Protecting Our Critical Infrastructure: A Role for Community Volunteers. Issue 10 (1st October 2014) - Spence, Shannon; Stephens, Scott
Abstract : Protecting our nation's critical infrastructure, including our reservoirs, dams, and other water conveyances, is essential to ensuring the safety of water ‐ our lifeblood. Most local governments are charged with this task, but funding constraints make constant facility monitoring difficult at best, especially when critical infrastructure is involved. Within the Austin Water Utility (AWU) in Texas, these constraints are all too real for its staff, who maintain 3, 672 miles of water transmission lines. AWU's residential and commercial infrastructure consists of 39 reservoirs and 45 pump stations maintained by a staff of 28 within the 538‐sq mi area served by AWU. At capacity the utility produces 335 mgd of water for the City of Austin and metro‐area customers. AWU has come up with a unique, low‐cost way to meet infrastructure monitoring needs by tapping into a reliable source of trained volunteers.